The impact of social security eligibility and pension wealth on retirement - Johan Sæverud (University of Copenhagen, Department of Economics, Center for Economic Behavior and Inequality (CEBI), 2024)
I investigate a Danish policy reform that postpones social security eligibility tied to an increase in life expectancy. The reform creates sharp discontinuities based on exact birth dates, allowing for the identification of causal effects. Using both administrative and survey data, I document a substantial increase in labor force participation of 20 percentage points as a result of postponing social security eligibility. The effect is strongest among individuals with low pension wealth. This pattern is consistent across multiple retirement age thresholds and cohorts, including both individuals who have already retired and in expectation for younger cohorts who are not yet retired. This research offers new insights into the impacts of life expectancy-based adjustments to social security eligibility. Welfare assessments show overall gains, but also that welfare effects are unequally distributed. Individuals with low pension wealth show the largest increases in labor supply, but also face the largest personal costs in terms of foregone consumption smoothing.
Keywords: J26; H55; 330; retirement; social security; labor supply